TNFR2: The new Treg switch? - José L. Cohen (OncoImmunology, 2018)
Three recent publications identified the TNF/TNR2 pathway as a new target to reduce graft-versus-host-disease through regulatory T cells activation or to potentially switch on a strong anti-leukemic effect through regulatory T cells blockade in allogeneic hematopoietic stem cell transplantation. This identified the TNF/TNR2 pathway as a swith and as a new target for immune checkpoint therapy to modulate the immune regulation in this clinical setting.